2017
DOI: 10.1111/cns.12709
|View full text |Cite
|
Sign up to set email alerts
|

Pituicytoma—An outlook on possible targeted therapies

Abstract: Pituicytomas were generally positive for VEGFR and showed regular expression of SSTR 3 and 5 indicating a possible treatment option through targeted therapies in cases where resection remains insufficient. Further research is necessary as to whether tumor growth can be inhibited using these pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A possible development of this tumor was also noticed from the FS cells. In a recent study, a positivity for vascular endothelial growth factor (VEGF) was detected in patients with pituicytoma (9).…”
Section: Trophic and Neurotrophic Factors In Human Pituitary Adenomasmentioning
confidence: 97%
“…A possible development of this tumor was also noticed from the FS cells. In a recent study, a positivity for vascular endothelial growth factor (VEGF) was detected in patients with pituicytoma (9).…”
Section: Trophic and Neurotrophic Factors In Human Pituitary Adenomasmentioning
confidence: 97%
“…Some authors suggest that stereotactic segmentation or conventional radiotherapy should be used systematically to control the residual tumor following subtotal resection of tumors [40], while others suggest that these treatments are limited to smaller tumors that do not affect visual acuity [41], but further data are needed to prove the effect. Recently, Mende et al indicated strong immunostaining for vascular endothelial growth factor receptor (VEGF-R) in a small series of patients with pituicytomas [14]. Based on these results, anti-VEGF-R therapy (bevacizumab) and somatostatin analogs may be promising treatment options, although their use has not yet been approved.…”
Section: Treatments and Outcomesmentioning
confidence: 99%
“…Pituicytoma, which is a low-grade neurogenic tumor (WHO I), is a very rare spindle-shaped astrocytic tumor that originates from the posterior lobe or stalk of the pituitary gland [9,10]. To date, only 4 articles have reported more than 6 cases of pituicytoma [11,12,13,14]. Thus, useful, detailed, and accurate information regarding the diagnosis and treatment of pituicytomas is di cult to obtain.…”
Section: Epidemiology and Clinical Characteristicsmentioning
confidence: 99%
“…Pituicytoma, which is a low-grade neurogenic tumor (WHO I), is a very rare spindle-shaped astrocytic tumor that originates from the posterior lobe or stalk of the pituitary [9,10]. Until now, only 4 articles have reported more than 6 cases of pituicytoma [11][12][13][14]. This makes it challenging to obtain useful, detailed, and accurate information regarding the diagnosis and treatment of pituicytomas.…”
Section: Epidemiology and Clinical Characteristicsmentioning
confidence: 99%
“…Some authors suggest that stereotactic segmentation or conventional radiotherapy should be used systematically to control tumor residue during subtotal resection of tumors [35], while others suggest that these treatments are limited to smaller tumors that do not affect visual acuity [36], but further data are needed to prove the effect. Recently, Mende et al has proved strong immunostaining of vascular endothelial growth factor receptor (VEGF-R) in a small series of pituicytoma [14]. Based on these results, anti-VEGF-R therapy (bevacizumab) and somatostatin analogues may be a promising treatment option, although its use has not yet been approved.…”
Section: Treatments and Outcomesmentioning
confidence: 99%